Analysis of the Contribution of TSS, pH, Fe, and Mn Parameters to the Pollution Load Capacity of Coal Mines in the Oal River, South Sumatra - Roy Sitorus; Eddy Ibrahim; Satria Jaya Priatna (Sriwijaya Journal of Environment, 2022)
The Oal River receives coal wastewater input at several companies. Coal mining in the vicinity of the location adds to the burden of water pollution in the Oal River due to waste water disposal activities. The increase in the concentration of coal waste and the pollution load that enters the Oal River water body will have an impact on the reducing capacity of the pollution load. This study aim to provide information on the condition of the pollution load carrying capacity of the Oal River. Determination of the carrying capacity of water pollution loads at water sources using the mass balance method. The characteristic of the Oal River water with the parameters TSS, pH, Fe and Mn have not yet passed the quality standards for river water and wastewater, both according to PP No. 22 of 2021 and South Sumatra Governor Regulation No. 8 of 2012. The Oal River still has the capacity to accommodate TSS and pH parameters.